Risk factors for frailty in elderly Japanese people who received Ningen Dock: a cross-sectional study - Mie Araki; Yuta Takahashi; Yoshiaki Ohyama; Ayumu Nagamine; Emiri Takahashi; Kunihiko Imai; Kunihiko Hayashi; Tetsuya Nakamura; Masahiko Kurabayashi; Kyoko Obayashi (SpringerOpen, 2022)
Abstract Background Frailty is a clinical condition characterized by increased vulnerability to adverse health outcomes. Elderly people are screened for frailty as part of preventative care. However, the risk factors for frailty among older adults who undergo Ningen Dock, a comprehensive medical checkup, remain unclear. Thus, this cross-sectional study aims to identify the risk factors for frailty in older adults who received Ningen Dock. The study included 372 participants over 65 years of age who underwent Ningen Dock at the Health Care Center of Gunma Chuo Hospital between April 2019 and March 2020. Frailty was defined using the Kihon Checklist, a basic checklist. Clinical variables were obtained from Ningen Dock records, a vascular function test, and a questionnaire on medication, among others. Multivariate ordinal logistic regression models were used to assess risk factors. Results Prevalence for frailty and pre-frailty was 12.6% and 26.6%, respectively. The mean age of participants was 72.0 ± 5.1 years old, and 43.5% were female. Compared with systolic blood pressure (SBP) ≥ 130 mmHg, the odds ratios for the 100-129 mmHg and < 100 mmHg groups were 2.43 (P = 0.020) and 8.95 (P <0.001). The odds ratio for the ≥ 7 medications group medications was 3.64 (P = 0.003) compared to 0-2 medications. Compared with serum iron ≥ 126 μg/dL, the odds ratio for ≤ 85 μg/dL was 2.91 (P = 0.002). The odds ratio for total bilirubin ≤ 0.6 mg/dL was 2.49 (P = 0.011) compared with > 0.6 mg/dL. Compared with an exercise habit of ≥ 4 metabolic equivalents (METs), the odds ratio for < 2 METs/week was 2.45 (P < 0.001). The odds ratio for the cardio-ankle vascular index (CAVI) ≥ 9 group was 1.84 (P = 0.020) compared to < 9. Conclusions In older adults who received Ningen Dock, SBP < 100 mmHg, medications ≥ 7, serum iron ≤ 85 μg/dL, total bilirubin ≤ 0.6 mg/dL, exercise habits < 2 METs, and CAVI ≥ 9 were associated with frailty.